2017
DOI: 10.1080/15287394.2017.1367143
|View full text |Cite
|
Sign up to set email alerts
|

5-Aza-2′-deoxycytidine, a DNA methylation inhibitor, induces cytotoxicity, cell cycle dynamics and alters expression of DNA methyltransferase 1 and 3A in mouse hippocampus-derived neuronal HT22 cells

Abstract: Epigenetic processes such as DNA methylation are essential for processes of gene expression in normal mammalian development. DNA methyltransferases (DNMT) are responsible for initiating and maintaining DNA methylation. It is known that 5-Aza-CdR, an inhibitor of DNMT induces cytotoxicity by reducing DNMT activity in various tumor cell lines. However, disturbances in neuronal DNA methylation may also play a role in altered brain functions. Thus, it was of interest to determine whether alterations in DNA methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…It was reported that tumor suppressive p53 and maspin repressed c-Myc activity through both transcriptional and posttranscriptional mechanisms, ultimately inhibiting cell growth 14 , 51 , 52 . Thus, it was reasonable to hypothesize that tumor suppressive maspin and the p53/p21 signaling pathway are involved in 5-Aza-induced antitumor activity 44 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that tumor suppressive p53 and maspin repressed c-Myc activity through both transcriptional and posttranscriptional mechanisms, ultimately inhibiting cell growth 14 , 51 , 52 . Thus, it was reasonable to hypothesize that tumor suppressive maspin and the p53/p21 signaling pathway are involved in 5-Aza-induced antitumor activity 44 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of 5-Aza-CdR co-treatment with sodium butyrate on DNMT3a and DNMT3b inhibition is significantly higher than that of 5-AzaCdR alone (Shen et al, 2008). In mouse hippocampus-derived neuronal HT22 cell line, 5-Aza-CdR down-regulates the expression of mRNA and protein DNMT1 and 3a (but no DNMT 3b) (Yang et al, 2017). In myelodysplastic syndrome (MDS), 5-Aza-CdR can re-activate the expression of the p15INK4B gene in MUTZ-1 cells by demethylation of the p15INK4B gene through inhibition of DNMT3a gene expression which is a mechanism of 5-Aza-CdR in the treatments of MDS (Tong et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…With this in mind, we intended to test whether DNA methyltransferases are involved in CE-mediated neuroprotective functions. 5-azacytidine (5-AZ), an analog of cytidine, effectively inhibits DNA methyltransferase and induces DNA hypomethylation ( Jiemjit et al., 2008 ; Yang et al., 2017 ). In the experiments, neurons were pretreated with 5-AZ followed by STS or CE treatment ( Figure 4 A and B, Supplementary Material Figure S8).…”
Section: Resultsmentioning
confidence: 99%